Heterotaxia - Situs ambiguo, síndrome de Ivermark o síndrome de asplenia-poliesplenia - Madrigal Jiménez, Sofía (2019)
Heterotaxia syndrome is a rare pathology that occurs due to a disruption during the embryonic development of the orientation of the axis, which can lead to multiple alterations in the presence, location and function of thoracoabdominal organs.